“An internal matter for the Soviet Union”. The attitude of the Polish Embassy in Moscow towards problems with changing the citizenship of Polish repatriates from the depths of the Soviet Union in 1945 - Marciniak, Wojciech (Przegląd Wschodnioeuropejski, 2023)
After concluding the Polish-Soviet repatriation agreement (6 July 1945), the Soviet Union (the USSR) started preparing for the evacuation of Polish exiles: victims of the Soviet deportation from the years 1940–1941. It soon became apparent that those who wanted to return to Poland were required to undergo the procedure of changing citizenship. The exiles had to prove they had been Polish citizens prior to 17 September 1939. The majority of them did not have the documents that could confirm this, thus, the planned repatriation was under threat. In the autumn of 1945, the Polish Embassy in Moscow took action to make the procedure of changing citizenship easier, and finally mass repatriation began.